(untitled) (Vietnam Journal of Community Medicine, 2021)
Knowledge and practice of mothers and caregivers are decisive factors in the prevention of Hand, Foot and Mouth disease for children under 5 years old. A cross-sectional descriptive study was used to assess the current status of knowledge and practice on prevention of Hand, Foot and Mouth disease among mothers/carers of children under 5 years old in Tu Nang commune, Yen Chau district, Son La province. Out of a total of 944 study subjects, 73% had correct knowledge about subjects at risk of disease, 84% knew about the danger of the disease and 81.4% knew about measures to prevent the spread. However, only 30.7% subjects had correct knowledge about taking care of children with Hand, Foot and Mouth disease. The rate of using antiseptic solution for cleaning utensils of children is low, accounting for only 13.1%. Correct practice of handling measures when children are sick and preventing infection ranges from 30.9 to 59.4%. And most of the study subjects practiced good environmental hygiene (92.8%).